Case Report: One case of pregnancy complicated by large cell neuroendocrine carcinoma of the cervix with syndrome of inappropriate secretion of antidiuretic hormone - Dong, Changhong; Zhu, Baoyu; Miao, Guoying; Zheng, Zhangcai (Frontiers in Oncology, 2025)
This article reports an extremely rare case of a 31-year-old pregnant woman diagnosed with large cell neuroendocrine carcinoma (LCNEC) of the cervix complicated by syndrome of inappropriate antidiuretic hormone secretion (SIADH). Admitted at 35+¹ weeks gestation due to vaginal bleeding, she was diagnosed with cervical LCNEC and pelvic lymph node metastasis. Following cesarean delivery, she developed severe hyponatremia (as low as 92 mmol/L) leading to coma during chemotherapy, meeting the criteria for SIADH. The hyponatremia was successfully corrected with the selective vasopressin V2 receptor antagonist tolvaptan. The patient subsequently achieved complete remission (CR) after concurrent chemoradiotherapy. However, the disease recurred with multiple metastases six months later. Despite multiple lines of therapy, she succumbed to multiple organ failure 19 months after initial diagnosis. This case highlights the highly aggressive nature and poor prognosis of LCNEC complicated by SIADH during pregnancy. Tolvaptan proved effective for the associated refractory hyponatremia but required careful monitoring to avoid sodium overcorrection. Dynamic serum sodium monitoring may serve as a potential biomarker for tumor recurrence. A review identified deficiencies in the management, including initial insufficient investigation into the cause of hyponatremia, aggressive fluid therapy exacerbating the condition, and delays in multidisciplinary collaboration and systemic therapy. This case underscores the critical importance of multidisciplinary collaboration and early, aggressive systemic treatment in managing such complex and rare malignancies.